Taoism, Teaching, and Learning A Nature-Based Approach to Education - Miller, John P. (University of Toronto Press, 2022)
The ancient Chinese philosophy of Taoism contains profound wisdom about the cosmos, nature, human life, and education. Taoism seeks to be in harmony with nature, and using it as a guide can help us live in a way that is healing to both ourselves and the planet. Taoism, Teaching, and Learning identifies key aspects of Taoist thought and highlights how these principles can promote a holistic approach to teaching and learning. In particular, this book offers educators guidelines and pedagogical examples for how to instil a perspective of interconnectedness into their classrooms. It sheds light on how philosophical Taoism articulates a vision of the universe and life that mirrors the actual realities of nature. Providing frameworks and methods for teaching and learning based on the interconnectedness of life, Taoism, Teaching, and Learning develops an inspiring vision for education and helps us to see our world in a deeply holistic and meaningful way.